Flavor SU(4) breaking between effective couplings - El-Bennich, Bruno [UNESP]; Krein, Gastão [UNESP]; Chang, Lei; Roberts, Craig D.; Wilson, David J. (American Physical Society (APS), 2012)
Using a framework in which all elements are constrained by Dyson-Schwinger equation studies in QCD, and therefore incorporate a consistent, direct and simultaneous description of light- and heavy-quarks and the states they constitute, we analyze the accuracy of SU(4)-flavor symmetry relations between πρπ, KρK, and DρD couplings. Such relations are widely used in phenomenological analyses of the interactions between matter and charmed mesons. We find that while SU(3)-flavor symmetry is accurate to 20%, SU(4) relations underestimate the DρD coupling by a factor of 5. © 2012 American Physical Society.